(untitled) (Archives of Pediatrics of Uruguay, 2022)
Introduction: in March 2020, the WHO declared the COVID-19 pandemic. In Uruguay, more than 60,000 children have had the disease, 500 of them requiring hospitalization. Three died. Objectives: to describe the epidemiological characteristics of children under 15 years of age diagnosed with COVID-19 controlled in an outpatient follow-up program, their epidemiological trace, and to compare results for 2020 and 2021. Methodology: descriptive study of children under 15 years of age with etiological confirmation of SARS-CoV-2 assisted by the program between March 2020 and June 2021. Variables: sex, age, origin, epidemiological link and symptoms. Variables were compared between the 2 study periods. Results: 1,328 patients were followed up, 663 (49.9%) male. Under 6 years old, 341 (25.6%), from 6 to 11, 608 (45.7%) and 12 years or older, 379 (28.7%). The epidemiological trace was mainly within the family (867 living together, 144 not living together). In 2020 there were 132 positive patients, 35 (26.5%) under 6 (1 under a year); 66 (50%) symptomatic: 49 upper respiratory symptoms (37.1%), 35 fever (26.5%), 7 headache (5.3%), 60 asymptomatic. In 2021, there were 1,196 positive patients, 306 (25%) under 6 (2 newborns and 43 under 1 year); 791 (66%) symptomatic: 500 upper respiratory symptoms (41.8%), 355 fever (29.7%), headache 212 (17.7%), 352 asymptomatic. In 2021, symptoms, headache and intrafamily infections increased (p < 0.05). The percentage of infections taking place at schools had a statistically significant decrease. Conclusions: in both periods, schoolchildren predominated, with cases appearing in children under one year of age in 2021. The children were infected at home. Symptomatic patients predominated in 2021, particularly those with headache.